Solução tecnológica alternativa para capacitação de produtores rurais: uso do podcast com vozes de inteligência artificial - Menezes, Francisca Tânia da Silva (Universidade Federal de Roraima, 2023)
With the growing expansion of new technologies around the world, it is necessary for communication to be more agile, in its most diverse forms, so that information and knowledge can reach people. One of these technologies that allows this agility is the podcast, which consists of transmitting content through audio on a specific theme or area. The objective of the present study was to prospect and analyze relevant information about the possibilities of use and the potential of this media, podcast, as an educational tool for training rural producers at an institution in the extreme north of Brazil, state of Roraima, which works directly with this target audience. The methodology used was exploratory, with bibliographical research and data analysis with a quali-quantitative approach, as well as the selection and use of free podcast creation tools -Anchor and the text-to-speech converter using Artificial Intelligence - Azure Microsoft . The results obtained revealed that the podcast has not yet been used as an educational tool for teaching and learning in rural areas, being characterized as an incremental innovation, and thus an alternative way of transmitting scientific technical knowledge and training rural producers, as well as how, its effectiveness was verified and that there is a possibility of applying it through the reproduction of technological contents already published in podcast format, offering applicable information and knowledge, with a podcast proposal called SABTEC, which is in the registration phase and production.